A study of the effects of isaxonine on vincristine-induced peripheral neuropathy in man and regeneration following peripheral nerve crush in the rat. Issue 9 (September 1985) - Le Quesne, P M; Fowler, C J; Harding, A E
Abstract : Administration of isaxonine (6 mg/kg powdered diet) had no effect on regeneration following sciatic nerve crush in the rat. In 10 patients undergoing treatment with vincristine (1.4 mg/m2 twice monthly) development of peripheral neuropathy was quantitated by neurological symptoms, signs and electrophysiological tests. Five also received isaxonine (1.5 g daily). All patients developed evidence of neuropathy, but in none was it severe. The three lowest disability scores were obtained in isaxonine treated patients, but the highest score was also in an isaxonine treated patient. The equivocal findings in this small study could not be amplified because the drug was withdrawn from clinical use on account of its hepatotoxicity.